Mechanical restoration of gravity instabilities in the Brunei margin, N.W. Borneo. (December 2018) - Berthelon, Josselin; Yuan, Xiaoping; Bouziat, Antoine; Souloumiac, Pauline; Pubellier, Manu; Cornu, Tristan; Maillot, Bertrand
Abstract: In offshore Brunei, the Baram delta displays Pliocene to recent gravitational deformations on top of the overpressured Setap Shales. We use the limit analysis, implemented in SLAMTec, to constrain their kinematics and propose first-order values of compatible pore pressures. Using the critical Coulomb wedge theory, we confirm that extreme overpressure are needed to account for the gravitational deformations currently observed in the delta. SLAMTec simulations quantify the role of the migration of the deltaic system on the deformations and suggest that this overpressure has existed since the initiation of the gravity-driven system. An inverse analysis is performed to identify the fluid overpressure and sedimentation pattern that best reproduces the forward structural model. This inverse approach validates the proposed kinematics, since we can reproduce quantities describing the structural style with overpressure coherent with the present-day observations. It points out the existence of key events explaining the structural interpretations, which leads to propose new kinematic models enriched with compatible pore pressure and sedimentation rates. This mechanical study highlights how mechanical modelling helps design a cross-section with an appropriate kinematics based on mechanical solutions and discuss on the basis of objective mechanical criteria the ranges of pore pressure consistent with a prescribed structural evolution. Highlights: Gravity instabilities in Brunei are linked with extreme fluid overpressure. Limit Analysis suggests that fluid overpressure exists since at least the Pliocene. An inverse approach validates the structural model based on mechanical solutions. Kinematic models enriched with pore pressure and sedimentation rates are proposed.